Analisis Dampak Covid-19 terhaap Perubahan Perilaku Konsumen pada Keputusan Pembeli secara Online (Studi Kasus: Masyarakat Kota Medan Penggunaan Layanan Shopee) - Sepfiani, Putri; Aslami, Nuri (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The Covid-19 pandemic is forcing people to work at home due to government policies to stay at home, including shopping. This study was conducted with the aim of knowing the causes of changes in consumer behavior in the people of Medan City during Covid-19. The approach in this study uses a descriptive qualitative approach with data analysis techniques carried out through the process of interviews, observations and literature studies. The population used in this study are people who often shop using shopee and the sample is the people of Medan city aged 18-40 years who often use shopee. The results of this study indicate that changes in consumer behavior towards purchasing decisions occur due to several factors, namely: Individuals, lifestyle, and convenience that is the cause of this happening. The community admits that the many conveniences provided by shopee in purchasing are the main attraction for the community, as well as new habits that occur during this pandemic such as the policy to stay at home and use the internet to meet daily needs, such as a trend during this pandemic.